Disparities and Trends in Birth Outcomes, Perinatal and Infant Mortality in Aboriginal vs. Non-Aboriginal Populations: A Population-Based Study in Quebec, Canada 1996–2010 - Chen, Lu (PLoS One, 2015)
BACKGROUND: Aboriginal populations are at substantially higher risks of adverse birth outcomes, perinatal and infant mortality than their non-Aboriginal counterparts even in developed countries including Australia, U.S. and Canada. There is a lack of data on recent trends in Canada. METHODS: We conducted a population-based retrospective cohort study (n = 254,410) using the linked vital events registry databases for singleton births in Quebec 1996–2010. Aboriginal (First Nations, Inuit) births were identified by mother tongue, place of residence and Indian Registration System membership. Outcomes included preterm birth, small-for-gestational-age, large-for-gestational-age, low birth weight, high birth weight, stillbirth, neonatal death, postneonatal death, perinatal death and infant death. RESULTS: Perinatal and infant mortality rates were 1.47 and 1.80 times higher in First Nations (10.1 and 7.3 per 1000, respectively), and 2.37 and 4.46 times higher in Inuit (16.3 and 18.1 per 1000, respectively) relative to non-Aboriginal (6.9 and 4.1 per 1000, respectively) births (all p<0.001). Compared to non-Aboriginal births, preterm birth rates were persistently (1.7–1.8 times) higher in Inuit, large-for-gestational-age birth rates were persistently (2.7–3.0 times) higher in First Nations births over the study period. Between 1996–2000 and 2006–2010, as compared to non-Aboriginal infants, the relative risk disparities increased for infant mortality (from 4.10 to 5.19 times) in Inuit, and for postneonatal mortality in Inuit (from 6.97 to 12.33 times) or First Nations (from 3.76 to 4.25 times) infants. Adjusting for maternal characteristics (age, marital status, parity, education and rural vs. urban residence) attenuated the risk differences, but significantly elevated risks remained in both Inuit and First Nations births for the risks of perinatal mortality (1.70 and 1.28 times, respectively), infant mortality (3.66 and 1.47 times, respectively) and postneonatal mortality (6.01 and 2.28 times, respectively) in Inuit and First Nations infants (all p<0.001). CONCLUSIONS: Aboriginal vs. non-Aboriginal disparities in adverse birth outcomes, perinatal and infant mortality are persistent or worsening over the recent decade in Quebec, strongly suggesting the needs for interventions to improve perinatal and infant health in Aboriginal populations, and for monitoring the trends in other regions in Canada.